Preclinical Testing of Chronic ICA-1S Exposure: A Potent Protein Kinase C-ι Inhibitor as a Potential Carcinoma Therapeutic - Christopher A. Apostolatos; Wishrawana S. Ratnayake; Sloan Breedy; Jacqueline Kai Chin Chuah; James Alastair Miller; Daniele Zink; Marie Bourgeois; Mildred Acevedo-Duncan (MDPI AG, 2024)
Protein kinase C-iota (PKC-ι) is an oncogene overexpressed in many cancer cells including prostate, breast, ovarian, melanoma, and glioma cells. Previous in vitro studies have shown that 5-amino-1-((1R,2S,3R,4R)-2-3-dihydroxy-4-(hydroxymethyl)cyclopentyl)-1H-imidazole-4-carboxamide (ICA-1S), a PKC-ι-specific inhibitor, has low toxicity in both acute and sub-acute mouse model toxicological testing and is an effective therapeutic against several cancer cell lines showing significant reductions in tumor growth when treating athymic nude mice with xenografted carcinoma cell lines. To further assess ICA-1S as a possible therapeutic agent, chronic mouse model toxicological testing was performed in vivo to provide inferences concerning the long-term effects and possible health hazards from repeated exposure over a substantial part of the animal's lifespan. Subjects survived well after 30, 60, and 90 days of doses ranging from 50 mg/kg to 100 mg/kg. Heart, liver, kidney, and brain tissues were then analyzed for accumulations of ICA-1S including the measured assessment of aspartate transaminase (AST), alkaline phosphatase (ALK-P), gamma-glutamyl transferase (GGT), troponin, and C-reactive protein (CRP) serum levels to assess organ function. Predictive in vitro/in silico methods were used to predict compound-induced direct hepatocyte toxicity or renal proximal tubular cell (PTC) toxicity in humans based on the high-content imaging (HCI) of compound-treated cells in combination with phenotypic profiling. In conclusion, ICA-1S shows low toxicity in both acute and chronic toxicology studies, and shows promise as a potential therapeutic.